Assessment of the Effects of Cooperation Among Lithuanian Colleges on Participants’ Network Intended for Human Resource Development - Šmergelienė, Valdonė (Ekonomika, 2007)
Recently, developed countries seem to be in transition to a society and economy based on the knowledge as well as on a new kind of information or. in other words, to knowledge society. The actions grounded on knowledge and solutions have occupied the place of natural events that are beyond human control in diverse and continually growing fields. As a result of these alterations, the focal assumption concerning economic-social boost merges into human resource development.Human resource development is to be defined as a process under which the activities of society. organizations, enterprises or individuals that are devoted to the evocation of behavioral changes arc achieved, sustained and modernized after having paid attention to cultural differences and cultural actions that affect this behavior, including education, training and encouragement of comprehension and skills in their common activities (cooperation). In the age of knowledge, the assumption of social-economic growth means human resource development. Furthermore, education, training and cooperation arc the most significant sources of human resource development that require a detailed theoretic and empiric research.The article aims at investigating the cooperation among Lithuanian colleges in Participants’ Network designed for human resource development. Hence the following objectives arise: to format the research model of participants’ network allocated to human resource development. and to provide the research results concerning cooperation among Lithuanian Colleges on Participants’ Network intended for human resource development.Through the analysis of participants’ network intended for human resource development. it is not only necessary to identify the participants and dimensions (such as the number of partners, the percentage of partners to whom it is possible to trusts an approximate term of cooperation frequency, the participants power and frequency of cooperation in various fields) of this network. but also the cooperation benefits as well as to investigate the relationship among the network dimensions and their effect on the benefits of the cooperation.The results have revealed that although the average number of public college partners is higher than of private ones. the approximate number of partners per one faculty or per one thousand of students at private colleges is higher or similar: public colleges trust their partners more than private ones; the public colleges cooperate with various partners for a longer time than private ones: public institutions cooperate with their partners more frequently than non-public ones; the power of public colleges is less than of non-public ones; the frequency of cooperation in various fields among public colleges is less than among non-public ones; public colleges value the benefits gained due to the cooperation less than non-public ones.In general, the network dimensions arc nut interdependent, i.e. the stronger the influence of the group in one of these criteria, the better the effects of other groups as well as common cooperation benefits. However, the effects of cooperation arc not related to any dimension on the network.